2015
DOI: 10.1371/journal.ppat.1004750
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis Virus Nonstructural Protein NS5 Interacts with Mitochondrial Trifunctional Protein and Impairs Fatty Acid β-Oxidation

Abstract: Infection with Japanese encephalitis virus (JEV) can induce the expression of pro-inflammatory cytokines and cause acute encephalitis in humans. β-oxidation breaks down fatty acids for ATP production in mitochondria, and impaired β-oxidation can induce pro-inflammatory cytokine expression. To address the role of fatty-acid β-oxidation in JEV infection, we measured the oxygen consumption rate of mock- and JEV-infected cells cultured with or without long chain fatty acid (LCFA) palmitate. Cells with JEV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 85 publications
0
23
1
Order By: Relevance
“…In recent years, viral RdRp proteins have also been reported to participate in multiple processes other than RNA synthesis. For example, in nearly all flaviviruses, NS5, the flaviviral RdRp protein, can inhibit pathways associated with IFN-I induction or signaling (52,53), while the Japanese encephalitis virus (JEV) NS5 protein can interact with the mitochondrial trifunctional protein and impairs fatty acid ␤-oxidation (54). Studies since the 1990s have indicated that expression of viral RdRp can activate the immune system and confer resistance to viral infection on plant cells (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, viral RdRp proteins have also been reported to participate in multiple processes other than RNA synthesis. For example, in nearly all flaviviruses, NS5, the flaviviral RdRp protein, can inhibit pathways associated with IFN-I induction or signaling (52,53), while the Japanese encephalitis virus (JEV) NS5 protein can interact with the mitochondrial trifunctional protein and impairs fatty acid ␤-oxidation (54). Studies since the 1990s have indicated that expression of viral RdRp can activate the immune system and confer resistance to viral infection on plant cells (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…HCV-induced loss of mitochondrial function also results in HIF-1α stabilization and a shift to glycolysis ( Ripoli et al, 2010 ). Similarly, Sindbis virus impairs both Complex I and II-linked respiration following replication, resulting in cell death ( Saks et al, 2012 ), while the Japanese Encephalitis Virus (JEV) protein NS5 disrupts β-oxidation through its interaction with hydroxyacyl-CoA dehydrogenase, thereby promoting virulence ( Khromykh et al, 2015 ). Interestingly, transcriptome profiling of MERS and SARS-CoV-infected bronchial epithelial cells also suggested a potential downregulation of the Complex I subunit NDUFA10 ( Guzzi et al, 2020 ).…”
Section: Viral Control Of Mitochondrial Dynamics and Metabolismmentioning
confidence: 99%
“…In addition to targeting fatty acid biosynthesis, viruses have been found to target the reverse catabolic process, fatty acid oxidation. HCMV and the Japanese encephalitis virus (JEV) inhibit fatty acid oxidation by targeting the mitochondrial trifunctional protein (MTP) which catalyzes fatty acid oxidation 33 , 34 . JEV inhibits MTP through its NS5 protein [33] , while HCMV redirects the cellular viperin protein to inhibit MTP [34] .…”
Section: Viral Targeting Of Core Metabolic Pathwaysmentioning
confidence: 99%
“…HCMV and the Japanese encephalitis virus (JEV) inhibit fatty acid oxidation by targeting the mitochondrial trifunctional protein (MTP) which catalyzes fatty acid oxidation 33 , 34 . JEV inhibits MTP through its NS5 protein [33] , while HCMV redirects the cellular viperin protein to inhibit MTP [34] . In contrast to these viruses that inhibit fatty acid oxidation, HCV infection requires fatty acid oxidation for its replication, which again highlights that certain aspects of viral metabolic manipulation are virus specific [35] .…”
Section: Viral Targeting Of Core Metabolic Pathwaysmentioning
confidence: 99%